Learning Islamic religious education based on digital literacy to strengthen students' religious character - Supandi Supandi; Ahmad Ahmad; Kurratul Aini; Akhmad Farid Mawardi Sufyan (UIN Salatiga, 2026)
This study analyzes the contribution of digital literacy-based Islamic Religious Education (IRE) learning to strengthening students' religious character at the Ummul Quro Putri Pamekasan Islamic Boarding School, Madura. Using a mixed-method sequential explanatory design, the study involved 100 student respondents in the quantitative phase and five informants in the qualitative phase, including a pesantren administrator, two IRE teachers, and two students. Quantitative data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling, while qualitative data were obtained through semi-structured interviews and analyzed thematically. The findings show that digital literacy significantly influences digital literacy-based IRE learning, which in turn strengthens students' religious character. Mediation analysis confirms that IRE learning acts as a significant mediator between digital literacy and religious character. Qualitative findings reveal that character strengthening is supported through teacher guidance, credible Islamic digital sources, digital tabayyun practices, ethical media use, and pesantren culture emphasizing discipline, responsibility, worship awareness, and moral conduct. This study positions digital literacy as a critical, ethical, and religious pedagogical strategy for developing digitally and morally competent Muslim students